Determinants of Green GDP in ASEAN-5 Countries - Hidayah, Nur; Wahyuningrum, Dinar; Kamara, Ibrahim Sorie; Rahmah, Jihan Lutfiyah (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2023)
The over-exploitation of natural resources to increase economic growth causes environmental degradation, and climate change has been a serious research issue. Gross Domestic Green Product (green GDP) is a proxy of Green economic growth. It is an indicator of sustainable economic development that considers aspects of environmental degradation. This study aims to determine the effect of carbon dioxide emissions, foreign direct investment, current account balance, and population on green GDP in five ASEAN countries: Indonesia, Malaysia, Thailand, the Philippines, and Myanmar. This study utilized panel data, a combination between time series and cross-section data. The panel data was examined by using the eViews 11 application. The selected model was the Fixed Effect Model (FEM). This study found that two independent variables: carbon dioxide emissions and the population had a significant positive effect on green GDP. Meanwhile, Foreign Direct Investment and current accounts do not significantly affect green GDP. Thus, the government as a regulator has a role in managing policies related to carbon emissions and population in supporting green economic growth.